Treosulfan compared to busulfan in allogeneic haematopoietic stem cell transplantation for myelofibrosis: a registry-based study from the Chronic Malignancies Working Party of the EBMT - Robin, Marie; Iacobelli, Simona; Koster, Linda; Passweg, Jakob R.; Avenoso, Daniele; Wilson, Keith M. O.; Salmenniemi, Urpu; Dreger, Peter; von dem Borne, Peter; Snowden, John A.; Robinson, Stephen; Finazzi, Maria Chiara; et al. (Bone marrow transplantation, 2024)
We aimed to compare outcomes following treosulfan (TREO) or busulfan (BU) conditioning in a large cohort of myelofibrosis (MF) patients from the EBMT registry. A total of 530 patients were included; 73 received TREO and 457 BU (BU ≤ 6.4 mg/kg in 134, considered RIC, BU > 6.4 mg/kg in 323 considered higher dose (HD)). Groups were compared using adjusted Cox models. Cumulative incidences of engraftment and acute GVHD were similar across the 3 groups. The TREO group had significantly better OS than BU-HD (HR:0.61, 95% CI: 0.39-0.93) and a trend towards better OS over BU-RIC (HR: 0.66, 95% CI: 0.41-1.05). Moreover, the TREO cohort had a significantly better Progression-Free-Survival (PFS) than both the BU-HD (HR: 0.57, 95% CI: 0.38-0.84) and BU-RIC (HR: 0.60, 95% CI: 0.39-0.91) cohorts, which had similar PFS estimates. Non-relapse mortality (NRM) was reduced in the TREO and BU-RIC cohorts (HR: 0.44, 95% CI: 0.24-0.80 TREO vs BU-HD; HR: 0.54, 95% CI: 0.28-1.04 TREO vs BU-RIC). Of note, relapse risk did not significantly differ across the three groups. In summary, within the limits of a registry-based study, TREO conditioning may improve PFS in MF HSCT and have lower NRM than BU-HD with a similar relapse risk to BU-RIC. Prospective studies are needed to confirm these findings.
Gesehen am 13.09.2024